VISUAL ESSAY: The Auteur and The Personal Comic: A Reconstruction of Online Identities - Gideon Kamang Frederick (Universitas Multimedia Nusantara, 2020)
When comic artist creates a personal comic, whose identities portrayed in the comic? Himself or his reconstructed image? More so, when the comic is published in social media, many viewers presumed that the comic is a mirror of the auteur life itself. This is where the constructed identities and real identities is reconstructed: negotiated, blurred between fiction and non-fiction.